2019
DOI: 10.1039/c9bm00274j
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating peptide together with PEG-modified mesostructured silica nanoparticles promotes mucous permeation and oral delivery of therapeutic proteins and peptides

Abstract: Electrostatic particle complexes, CPP/TPP/NP, consisting of PEG-modified silica NPs with TPP and CPP, showed satisfactory stability and mucous penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…In this respect, Tan et al recently presented CPP-PEG-modified mesostructured silica NPs that greatly enhanced the bioavailability of therapeutic peptides and proteins. Significantly promoted mucous permeation and oral availability of drug payloads were observed and demonstrated the potential of their study for future developments in this direction [55].…”
Section: Current State-of-the-art and Future Perspectivesmentioning
confidence: 93%
See 1 more Smart Citation
“…In this respect, Tan et al recently presented CPP-PEG-modified mesostructured silica NPs that greatly enhanced the bioavailability of therapeutic peptides and proteins. Significantly promoted mucous permeation and oral availability of drug payloads were observed and demonstrated the potential of their study for future developments in this direction [55].…”
Section: Current State-of-the-art and Future Perspectivesmentioning
confidence: 93%
“…To date, the often strong positive net charge of CPPs has been exploited for their self-assembly on the surface of negatively charged nanostructures. For instance, Tan and co-workers prepared mesoporous silica particles with strong negative zeta potential (−32 mV) and large pores up to 11 nm, which they used for the noncovalent loading with penetratin [55]. Lower loading rates of CPPs were observed after precedent surface modifications of silica particles with polyethylene glycol (PEG) (average molecular weight 4000 and 10,000, respectively), presumably related to the increase in zeta potential, as well as shielding effects of long PEG chains.…”
Section: Non-covalent Attachmentmentioning
confidence: 99%
“…ese molecules include cell penetrating peptide (CPP), avidin-biotin, saccharides, and transferrins [116][117][118]. Tan et al found that CPP mainly affects transport and exocytosis, whereas PEG polymer influences mucus penetration [119]. Approaches to overcome this limitation while still maintaining the advantages of PEG have been tested, such as preparing PEG covalently linked to 1,2dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE).…”
Section: Np Surface Coatings and Tumor Penetrationmentioning
confidence: 99%
“…We previously showed that these peptides, while engaging with different cellular receptors, invoke a similar macropinocytosis-like process for cell entry 19,26 . Besides assisting the NP uptake, these CPPs were also used to lead NPs from one cell to another 16,27 , and may help elucidate the function of ligand-receptor interactions during intercellular exchange.…”
Section: Resultsmentioning
confidence: 99%